2008
DOI: 10.1002/bjs.6232
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of colonic irrigation for the treatment of defaecation disorders

Abstract: Background: Retrograde colonic irrigation is a possible treatment for defaecation disorders when conservative treatment or surgery has failed. The aim of this prospective study was to investigate its effectiveness. Results: The study included 39 patients (26 women; mean age 58·0 years). In group A, 11 of 18 patients were pseudocontinent for faeces at 3 months (P < 0·001). Parks' incontinence scores decreased for all patients in this group at 3 months (P < 0·001), 6 months (P = 0·036) and 1 year (P = 0·005). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 38 publications
0
40
1
Order By: Relevance
“…Although some reports showed success rates up to 90 % for both constipation and faecal incontinence [14], none of our patients had undergone Advantages of ventral rectopexy (VR) consist in the mobilization of the rectovaginal space down to the levator ani muscle and the anterior placement of a mesh, which is sutured distally to the anterior wall of the rectum as well as to the posterior wall of the vagina, and secured proximally to the sacral promontory [1]. In contrast to other methods of repair, posteriorly only a small patch of the promontorium needs to be freed with little risk of the more laterally running hypogastric nerves.…”
Section: Discussionmentioning
confidence: 95%
“…Although some reports showed success rates up to 90 % for both constipation and faecal incontinence [14], none of our patients had undergone Advantages of ventral rectopexy (VR) consist in the mobilization of the rectovaginal space down to the levator ani muscle and the anterior placement of a mesh, which is sutured distally to the anterior wall of the rectum as well as to the posterior wall of the vagina, and secured proximally to the sacral promontory [1]. In contrast to other methods of repair, posteriorly only a small patch of the promontorium needs to be freed with little risk of the more laterally running hypogastric nerves.…”
Section: Discussionmentioning
confidence: 95%
“…Patients with multiple sclerosis have also been included in other studies with mixed patient populations, but their outcomes have not been reported separately. 19,22,32 The 10-year follow-up studies in adults and children 20,21 included some patients with multiple sclerosis. Overall, reported success rates were 40% for patients (n ¼ 25) using a rectal balloon catheter, cone-shaped colostomy tip or other systems, 20 and 50% for patients (n ¼ 10) using either Peristeen or a cone-shaped colostomy tip.…”
Section: Efficacy Of Tai In Patients With Sci or Cauda Equinamentioning
confidence: 99%
“…Other reports have documented the use of TAI after anterior resection 35,36 or after dynamic graciloplasty, 37 and various studies have enrolled mixed patient populations, including patients with a history of abdominal surgery, idiopathic (neurogenic) bowel dysfunction, irritable bowel syndrome, anorectal malformation, coloanal anastomosis, diabetes mellitus, multiple sclerosis, SCI and neural tube closure defect. 29,32,34,38,39 Owing to the heterogeneous nature of these mixed patient populations and the low number of patients of each type, further investigation is required to confirm the efficacy of TAI in each of these settings. The potential of TAI in the treatment of the very distressing low anterior resection syndrome is of particular interest and merits further investigation, although this will need a cautious approach to avoid the possibility of perforation in this at-risk group.…”
Section: Efficacy Of Tai In Other Populationsmentioning
confidence: 99%
“…Transanal irrigation improves bowel function in adult patients with fecal incontinence or constipation. [7][8][9][10] Recent clinical trials in adults with spinal cord injury and neurogenic bowel dysfunction (NBD) clearly showed the benefits of this procedure. [11][12] Compared with best supportive bowel management without irrigation, patients with transanal irrigation had less constipation, less fecal incontinence and improved symptom-related quality of life (QoL).…”
Section: Introductionmentioning
confidence: 99%